Topics in dynamics of civil structures, volume 4 : proceedings of the 31st IMAC, a conference on structural dynamics, 2013 - Pakzad, Shamim; Racic, Vitomir; Pavic, Aleksandar; Reynolds, Paul; Catbas, Fikret Necati (Conference Proceedings of the Society for Experimental Mechanics Series, 2013)
Topics in Dynamics of Civil Structures, Volume 4: Proceedings of the 31st IMAC, A Conference and Exposition on Structural Dynamics, 2013, the fourth volume of seven from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on:   Modal Parameter Identification for Civil Structures Vibration Control of Civil Structures Cable Dynamics Damage Detection Models for Civil Structures Data-Driven Health Monitoring of Structures & Infrastructure Experimental Techniques for Civil Structures Human-induced Vibrations of Civil Structures Structural Modeling for Civil Structures